Using WhatsApp Focus Group Discussions for Qualitative Data Collection: Exploring Knowledge, Attitudes, and Perceptions of COVID-19 in Singapore. (8th April 2022) - Neo, Pearlyn HM; Lim, Jane M; Tan, Rayner KJ; Ong, Suan Ee
This qualitative study aimed to explore Singapore residents' knowledge, attitudes, perceptions, and behaviors around COVID-19 as shaped by different information sources. Through utilizing WhatsApp as a means of conducting digital focus group discussions (FGDs), participants were involved in five consecutive days of discussions through both synchronous and asynchronous means. We found that the use of WhatsApp as a means of conducting FGDs not only served as a means of generating essential, time-sensitive data in the community, but also advanced the quality and quantity of data generated, democratized, and enhanced the participatory nature of FGDs, and facilitated the communication of potential issues around data privacy between facilitators and participants. Although challenges around privacy and confidentiality remain, this means of collecting data is novel in terms of providing timely and relevant data during a pandemic and would be appropriate to be further utilized in the context of other health-related research beyond a public health emergency.